Fundamentals for magnetic patterning by ion bombardment of exchange bias layer systems - Ehresmann, A.; Engel, D.; Weis, T.; Schindler, A.; Junk, D.; Schmalhorst, J.; Höink, V.; Sacher, Marc; Reiss, G. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.

Optical properties of disordered metallic photonic crystal slabs - Nau, D.; Schönhardt, A.; Christ, A.; Zentgraf, Thomas; Bauer, Ch.; Kuhl, J.; Giessen, H. (physica status solidi (a))

Spin-controlled LEDs and VCSELs - Hövel, S.; Gerhardt, N. C.; Brenner, C.; Hofmann, M. R.; Lo, F.-Y.; Reuter, Dirk; Wieck, A. D.; Schuster, E.; Keune, W. (physica status solidi (a))

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Tuneable photonic crystals obtained by liquid crystal infiltration - Kitzerow, Heinz-Siegfried; Lorenz, A.; Matthias, H. (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Microscopic analysis of the optical and electronic properties of semiconductor photonic‐crystal structures - Pasenow, B.; Reichelt, Matthias; Stroucken, T.; Meier, Torsten; Koch, S.W. (physica status solidi (a))
The combination of dielectric photonic crystals and semiconductor nanostructures makes it possible to design many important aspects of the optoelectronic system response. A spatially-varying dielectric environment induces modifications of the transversal and the longitudinal components of the electromagnetic field which have to be included in the self-consistent microscopic analysis of the optical properties of hybrid semiconductor photonic-crystal structures. In this paper, the development of a semiclassical microscopic theory is reviewed. Whereas the classical electromagnetic field is described at the level of Maxwell's equations, a full many-body quantum theory is used for the interacting electronic excitations in the semiconductor material. Relevant examples of the numerical solutions of the resulting Maxwell semiconductor Bloch equations are presented showing, e.g., characteristic modifications of excitonic absorption spectra, the spatio-temporal dynamics of electronic wave packets, as well as an increase of the optical gain in properly designed device geometries.

Reference Models and Modeling Languages for Product-Service Systems --- Status-Quo and Perspectives for Further Research - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Proceedings of the 41th Hawai'i International Conference on System Sciences)

Quantum Hall effect in long and in mobility adjusted GaAs/AlxGa1-xAs samples - Diaconescu, D.; Goldschmidt, A.; Reuter, Dirk; Wieck, A. D. (physica status solidi (b))

Theoretical study of phononassisted singlet-singlet relaxation in two-electron semiconductor quantum dot molecules - Grodecka, Anna; Machnikowski, Paweł; Förstner, Jens (physica status solidi (c))
Phonon-assisted singlet-singlet relaxation in semiconductor quantum dot molecules is studied theoretically. Laterally coupled quantum dot structures doped with two electrons are considered. We take into account interaction with acoustic phonon modes via deformation potential and piezoelectric coupling. We show that piezoelectric mechanism for the considered system is of great importance and for some ranges of quantum dot molecule parameters is the dominant contribution to relaxation. It is shown that the phonon-assisted tunneling is much faster (down to ∼ 6 ps even at zero temperature) in comparison with other decoherence processes. The influence of Coulomb interaction is discussed and its consequences are indicated. We calculate the relaxation rates for GaAs quantum dot molecules and study the dependence on quantum dot size, distance and offset between the constituent quantum dots. In addition the temperature dependence of the tunneling rates is analyzed.
Keywords: tet_topic_qd

Development status and market potential of hot formed ballistic steels - Tröster, Thomas; Howe, C.; Müller, M.; Rostek, W.

On the graphitisation role of oxide supports in carbon nanotube CVD synthesis - Rümmeli, M. H.; Schäffel, F.; de los Arcos de Pedro, Maria Teresa; Haberer, D.; Bachmatiuk, A.; Kramberger, C.; Ayala, P.; Borowiak-Palen, E.; Adebimpe, D.; Gemming, T.; Leonhardt, A.; Rellinghaus, B.; et al. (physica status solidi (b))

Dielectric layers for organic field effect transistors as gate dielectric and surface passivation - Diekmann, T.; Pannemann, C.; Hilleringmann, Ulrich (physica status solidi (a))
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)

Non-polar cubic AlGaN/GaN HFETs grown by MBE on Ar+implanted 3C-SiC (001) - Tschumak, Elena; Lindner, Jörg; Bürger, M.; Lischka, K.; Nagasawa, H.; Abe, M.; As, Donald (physica status solidi (c))
The growth of cubic group III-nitrides is a direct way to eliminate polarization effects, which inherently limit the fabrication of normally-off heterojunction field-effect transistors (HFETs) in GaN technology. HFET structures were fabricated of non-polar cubic AlGaN/GaN hetero layers grown by plasma assisted molecular beam epitaxy (MBE) on free standing 3C-SiC (001). The electrical insulation of 3C-SiC was realised by Ar+ implantation before c-AlGaN/GaN MBE. The structural properties of the epilayers were studied by highresolution x-ray diffraction (HRXRD). HFETs with normally off and normally-on characteristics were fabricated of cubic AlGaN/GaN. Capacitance-voltage (CV) characteristics of thegate contact were performed to detect the electron channel at the c-AlGaN/GaN hetero interface.

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

The physics of highly ordered molecular rows - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Ab initioinvestigation of the LiNbO3(0001) surface - Sanna, Simone; Gavrilenko, Alexander V.; Schmidt, Wolf Gero (physica status solidi (c))

Dissociative and molecular adsorption of water onα-Al2O3(0001) - Wippermann, S.; Schmidt, Wolf Gero; Thissen, P.; Grundmeier, Guido (physica status solidi (c))